A de novo synonymous variant in EFTUD2 disrupts normal splicing and causes mandibulofacial dysostosis with microcephaly: case report - Arthur Jacob; Jennifer Pasquier; Raphael Carapito; Frédéric Auradé; Anne Molitor; Philippe Froguel; Khalid Fakhro; Najeeb Halabi; Géraldine Viot; Seiamak Bahram; Arash Rafii (BMC Medical Genetics, 2020)
Abstract Background Mandibulofacial dysostosis with microcephaly (MFDM) is a rare autosomal dominant genetic disease characterized by intellectual and growth retardations, as well as major microcephaly, induced by missense and splice site variants or microdeletions in the EFTUD2 gene. Case presentation Here, we investigate the case of a young girl with symptoms of MFDM and a normal karyotype. Whole-exome sequencing of the family was performed to identify genetic alterations responsible for this phenotype. We identified a de novo synonymous variant in the EFTUD2 gene. We demonstrated that this synonymous variant disrupts the donor splice-site in intron 9 resulting in the skipping of exon 9 and a frameshift that leads to a premature stop codon. Conclusions We present the first case of MFDM caused by a synonymous variant disrupting the donor splice site, leading to exon skipping.